1998
DOI: 10.1111/j.1346-8138.1998.tb02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Milieu in the Maintenance of Melasma in Fertile Women

Abstract: Melasma is a specific type of facial hyperpigmentation seen in women taking oral contraceptives, in non-pregnant women who have not used oral contraceptives, and in some pregnant women during the progression of gestation, but rarely in men. Circulating LH, FSH, PRL, and E2-17 beta on day 5, 7, 9, and 11 of the menstrual cycle and progesterone (P) on day 17, 19, and 21 were measured in thirty-six ovulating women with melasma (study group) age 25-35 years and twelve healthy controls (control group). Twenty-seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
3
18
1
1
Order By: Relevance
“…In our study out of 66 patients oestrogen level of 18 (27.3%) patients was found to be normal, while that of 48 (72.7%) was found to be deranged with either an increase or decrease, mostly increased in the estradiol levels. This is similar to the study of Khalid Mahmood et al [7] in which 89.1% showed deranged values of oestrogen (Mostly increased), while Jee et al [8] reported a dose-dependent proliferation of melanocytes in culture after 17β-estradiol addition, despite a decrease of tyrosinase activity and melanin content, Hassan I et al [9] observed higher levels of E2-17β on 5, 7, 9 day in the study group indicating a possible role of high E2-17β in the maintenance of melasma, and Kim NH et al [10] showed down-regulation of H19 and the development of melasma with a sufficient dose of oestrogen treatment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study out of 66 patients oestrogen level of 18 (27.3%) patients was found to be normal, while that of 48 (72.7%) was found to be deranged with either an increase or decrease, mostly increased in the estradiol levels. This is similar to the study of Khalid Mahmood et al [7] in which 89.1% showed deranged values of oestrogen (Mostly increased), while Jee et al [8] reported a dose-dependent proliferation of melanocytes in culture after 17β-estradiol addition, despite a decrease of tyrosinase activity and melanin content, Hassan I et al [9] observed higher levels of E2-17β on 5, 7, 9 day in the study group indicating a possible role of high E2-17β in the maintenance of melasma, and Kim NH et al [10] showed down-regulation of H19 and the development of melasma with a sufficient dose of oestrogen treatment.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, prolactin level was found normal in 59 (89.4%) and deranged in 7 (10.6%) of the patients. This is higher than the study of Khalid Mahmood et al [7] in which prolactin levels were normal in 134 (97.1%) patients and deranged in 4 (2.9%), while Hassan I et al [9] revealed decreased and Pérez et al [13] found normal prolactin levels on 9 th day of cycle.…”
Section: Prolactincontrasting
confidence: 54%
“…There were differences in the levels of 17-β-estradiol at the beginning of the menstrual cycle among the groups, suggesting that circulating estrogens may constitute a risk factor and 'maintainer' of the disease. 65 …”
Section: Etiology Physiopathology and Risk Factorsmentioning
confidence: 99%
“…Although the pathogenic mechanism is unknown, luteinizing hormone and progesterone may be involved, because melasma occasionally appears on women who take contraceptive pills, does not appear on women after menopause, and is related to pregnancy. 1,2) Moreover, it may be induced by exposure to ultraviolet (UV) radiation, especially UVA in sunlight. 3) Treatments include topical application of a depigmenting agent, hydroquinone 4) and chemical peeling using glycolic acid.…”
Section: Introductionmentioning
confidence: 99%